Assessment of service refinement and its impact on repeat HIV testing by client's access to Australia's universal healthcare system: a retrospective cohort study. Issue 8 (4th August 2019) - Ryan, Kathleen E; Wilkinson, Anna L; Asselin, Jason; Leitinger, David P; Locke, Peter; Pedrana, Alisa; Hellard, Margaret; Stoové, Mark
Abstract: Introduction: Achieving the virtual elimination of HIV requires equitable access to HIV prevention tools for all priority populations. Restricted access to healthcare means migrants face particular barriers to HIV prevention services. In February 2016, a peer‐led rapid HIV testing service for gay, bisexual and other men who have sex with men (gay and bisexual men, GBM) in Melbourne, Australia, introduced free sexually transmissible infection (STI) testing funded through Medicare (Australia's universal healthcare system). Medicare ineligible migrant clients were required to pay up to $158AUD for STI tests. We determined the uptake of STI testing and assessed the impact on repeat HIV testing among Medicare eligible and ineligible clients. Methods: All HIV tests conducted between August 2014 and March 2018 were included. We describe client characteristics, STI testing uptake and HIV/STI positivity among Medicare eligible and ineligible clients. Repeat HIV testing, assessed as the percentage of HIV tests with a return test within six months, was compared pre‐integration (August 2014‐June 2016) and post‐integration(July 2016‐March 2018) of STI testing using segmented linear regression of monthly aggregate data for Medicare eligible and ineligible clients. Results: Analyses included 9134 HIV tests among 4753 individuals. Medicare ineligible clients were younger ( p  < 0.01), and fewer reported previously testing for HIV ( p  < 0.01) and high HIV risk sexual behaviours. There was no difference in HIV positivity between the two groups ( p  = 0.09). STI testing uptake was significantly lower among Medicare ineligible clients (7.6%, 85.3%; p  < 0.01). Following STI testing introduction there was an immediate increase in six‐month return HIV testing (6.4%; p  = 0.02) and a significantly increasing rate of return HIV testing between July 2016 and March 2018 (0.5% per month; p  < 0.01) among Medicare eligible clients but no immediate change in return testing (−0.9%; p = 0.7) or the rate of change in return testing between July 2016 and March 2018 (0.1% per month; p  = 0.3) among Medicare ineligible clients. In March 2018, six‐month return HIV testing was 52.3% and 13.2% among Medicare eligible and ineligible clients respectively. Discussion: Improvements in return HIV testing observed among Medicare eligible clients did not extend to Medicare ineligible clients highlighting the impact of inequitable access to comprehensive sexual healthcare on test‐and‐treat approaches to HIV prevention.